Transcriptional analysis of the Pseudomonas aeruginosa genes algR, algB, and algD reveals a hierarchy of alginate gene expression which is modulated by algT. - Wozniak, D J (1994)
Strains of Pseudomonas aeruginosa which colonize and infect the lungs of cystic fibrosis patients have a mucoid colony morphology due to the overproduction of the exopolysaccharide alginate. The response regulators AlgB and AlgR are required for the transcription of algD, a tightly regulated gene encoding GDP-mannose dehydrogenase, which is critical for P. aeruginosa alginate biosynthesis. Previous studies indicated that mutations in the algT gene of mucoid FRD1 P. aeruginosa result in nonmucoid derivatives. However, the specific role for algT in alginate gene regulation has not been elucidated. In this study, transcription of algB, algD, and algR was characterized by gene fusion and primer extension analysis. Expression of algR and algD was abolished in P. aeruginosa strains containing algT::Tn501 insertions because of lack of transcription initiation at the algR and algD promoters. An algR mutation was constructed in FRD1, and this resulted in the loss of alginate production and a dramatic decrease in algD transcription. RNA and gene fusion analysis revealed that algB is not required for algR expression, nor is algR necessary for transcription of algB. Thus, with the exception of a requirement for AlgT, the AlgB and AlgR pathways appear to be independent of each other. In gel band mobility shift assays, a protein(s) present in extracts from mucoid and algB and algR mutant P. aeruginosa strains formed a specific complex with algD sequences located immediately upstream of the start of transcription. No binding to these sequences was observed when extracts from algT mutant strains were examined. A model proposed suggests that a hierarchy of alginate gene expression exists in which AlgT is required for transcription of the response regulators algB and algR, which in turn are necessary for algD expression. AlgT or a protein under algT control also binds to sequences located within the algD promoter.